O cotidiano de trabalho do ACS: trilhando caminhos entre prescrições e invenções - Barros, Luciana Soares de [UNIFESP] (2016)
Introduction: This study focus on the work process of the Community Health Agents (ACS), an strategic actor in Brazilian National Health System (SUS) due to its role as “mediator”; between the community and the Primary Care Unit Health (UBS). Objective: This study aims give visibility to elements in the daily work of ACS, trying to understand how he organizes his care practices; builds his relationship with the health team; reflects on their performance in the context of the Family Health Strategy; and the main difficulties encountered to carry out his work. Method: Cartographic method made by participant observation in six UBS of the metropolitan region of São Paulo city that provides the production of field diaries with records of scenes observed in team meetings, group activities, home visits, walking through the territories and other activities. For analysis the concept of “visibility plan”; was used, which means what is highlighting or becomes visible / speakable from the connections of the scenes of similar “nature”; as recorded in field diaries. Results and discussion: From the visibility plans was possible to discuss issues relating to acquaintanceship of ACS with the refusal of the population; to violence and drug trafficking in the territory; to the difficult management of the community’s secrets; and to the multiple dimensions of the complex relationship with the community due to his dual resident / worker status. It was possible to understand a process of transformation of this worker, which has been presented as a multipurpose worker at UBS, occupying the role on an interim manner. This is different from the profile idealized by the ACS policy, which has a certain “militancy”; as a constitutive characteristic of the function. In addition it highlights the connection of the ACS with the rationalization of health practices, that has as elements the bureaucratization and the setting of production targets, increasing his work overload, but also his strategies to handle the flows, exercising their autonomy in the territory. The relationship of ACS with the health team points to domination and subordination of ACS, but also to his resistance movements, inventiveness and cooperative work. Conclusion: This study has highlighted a health worker in mutation that reproduces biomedical and bureaucratic practices, which can disfigure his role as a community link, but can also be quite creative, permanently (re)inventing his practices, in a way much more complex than prescribed in the original formulation of health policy, due, among other things, the complexity of the territories in which he operates.